Colletotrichum blight control in large cardamom (Amomum subulatum Roxb.) nursery - A K Biswas, M R Sudharshan, K A Saju, R Kuldeep, T N Deka, U Gupta, (Journal of Spices and Aromatic Crops, 2013)
Experiments were conducted in large cardamom (Amomum subulatum Roxb.) nursery using bioagents and chemicals to produce healthy planting materials free from blight caused by Colletotrichum gloeosporioides (Penz.) Sacc. The results indicated that selection of apparently disease free mother plants and treating the rhizome and pseudostem (planting unit) with carbendazim+mancozeb (0.3%) or copper oxychloride (0.3%) would help in reducing the disease incidence in the nursery. Since Sikkim is an organic state, use of copper oxychloride can be recommended.